History of Zarraga (Duog sang marimis nga pantat kag malapad nga parayan). - Ganancial, Karen P.
Zarraga as a fourth class municipality still has a long way in developing its industries. Paray industry is one of the major industries of the town. Having a vast area of land, Zarraga is one of the big contributors of paray in the whole province of Iloilo and of the Region. Paray production before was very abundant due to copious source of water from creeks and irrigation. However, due to some changes caused by climate and the use of hazardous farm chemicals, the number of paray production decreases as time goes by. Zarraga is now facing problem due to the frequent emergence of subdivisions which led to the conversion of agricultural land to commercial and residential lands which has an effect on the production of paray., Aside from paray production, many Zarraganhons depend in pantat cultivation. This emerging industry receives little or no support at all from the local government. Pantat growers rely with each other in terms of crisis. Pantat production is very abundant during rainy season for there is an abundant supply of water. However, pantat growers suffer during dry season because of the scarcity of water that can cause sickness to pantat. During this time also that Zarraga experience pantat shortage for seldom pantat barbecues are sold in the streets. In this study, the researcher interviewed some residents in Zarraga such as pantat growers, farmers as well as some government employees in institutions such as BFAR, Department of Agriculture in Zarraga, Municipal Engineering Office and Municipal Planning and Development Office. Base on the data that the researcher acquired, it is recommended to the local government unit of Zarraga to give focus on its pantat and paray industries for these industries are the major source of livelihood of many Zarraganhons. The number of farmers and pantat growers increases every year which simply say that these two industries have a great contribution with regards to the economic aspect of the town.